2002
DOI: 10.1021/jf011338v
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Level, and Behavior of Aflatoxins during Coffee Bean Roasting and Decaffeination

Abstract: Screening for aflatoxins (Afs), isolation and identification of Aspergillus flavus, and the effect of decaffeination and roasting on the level of contamination in coffee beans are studied. The percent frequency of A. flavus ranged between 4 and 80% in green coffee beans (GCB), whereas in ground roasted coffee beans (GRCB), it ranged between 1 and 71%. Aflatoxins were detected in 76.5 and 54.6% of the infected samples with averages of 4.28 and 2.85 microg/kg of GCB and GRCB, respectively. Roasting was demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 18 publications
4
29
2
2
Order By: Relevance
“…Ogunswanwo et al [18] reported a mean 81.7% total aflatoxin reduction after roasting peanuts at 150˚C for 30 minutes. That roasting reduces aflatoxin concentration significantly has also been reported in coffee production at the roasting stage [21] and in pistachio nuts [22].…”
Section: Discussionsupporting
confidence: 56%
“…Ogunswanwo et al [18] reported a mean 81.7% total aflatoxin reduction after roasting peanuts at 150˚C for 30 minutes. That roasting reduces aflatoxin concentration significantly has also been reported in coffee production at the roasting stage [21] and in pistachio nuts [22].…”
Section: Discussionsupporting
confidence: 56%
“…An epoxide hydrolase gene was also found in the genome. Epoxides can be generated by P450s, and if a molecule such as aflatoxin (which has been reported in coffee seeds 41 ) is present, will produce a compound that will intercalate into DNA and result in toxic DNA effects 42 . Epoxide hydrolases will break this epoxide and prevent such adverse reactions on the DNA 42 .…”
Section: Resultsmentioning
confidence: 99%
“…The Table 2 shows the OTA production by the isolates in two mediums. The YES and MEA mediums have been successfully employed to verify the production of mycotoxins in vitro (Soliman, 2002;Batista, Chalfoun, Prado, Schwan, & Wheals, 2003;Taniwaki, Pitt, Teixeira, & Iamanaka, 2003;Ritter & Noll, 2008).…”
Section: Microbiological Analysismentioning
confidence: 99%